2015
DOI: 10.3126/jkmc.v3i4.13370
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of neonates admitted to the Neonatal Care Unit at a teaching hospital in Lalitpur, Nepal

Abstract: Background: Neonatal period is a vulnerable time in which the newborn has to adapt to a totally new environment and is susceptible to many problems, which may even be life threatening. It is found that neonatal mortality rate is decreasing in Nepal but at a slower pace than infant and child mortality. In order to improve neonatal outcome, it is crucial to identify the areas where health care can be improved. Objectives:This study was conducted to analyze the spectrum of diseases and outcomes at a level two NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 6 publications
6
22
2
Order By: Relevance
“…Strengthening of antenatal, intra-partum and post partum care is very important to combat these complications. There were 1.9% mortalities and 3.4% referrals during study period collaborating with the findings of Shakya et al [15] Mortality rates were found higher (13.7%-27%) in some studies probably due to more number of preterm babies and sicker neonates. [16] Commonest cause for mortality was birth asphyxia in accordance with literature reports.…”
Section: Discussionsupporting
confidence: 86%
“…Strengthening of antenatal, intra-partum and post partum care is very important to combat these complications. There were 1.9% mortalities and 3.4% referrals during study period collaborating with the findings of Shakya et al [15] Mortality rates were found higher (13.7%-27%) in some studies probably due to more number of preterm babies and sicker neonates. [16] Commonest cause for mortality was birth asphyxia in accordance with literature reports.…”
Section: Discussionsupporting
confidence: 86%
“…These babies need immediate neonatal care to prevent death and hence focus should be on prevention of LBW babies [14]. The male preponderance in this study is similar to other studies [15][16][17]. This may be because of vulnerability of male neonates and gender preference.…”
Section: Discussionsupporting
confidence: 78%
“…The main causes of admission in this study were neonatal sepsis, birth asphyxia and hyperbilirubinemia which in accordance with other studies conducted in Nepal. [8][9][10] Based on the treatment services offered to the sicknewborn, the health facilities are classified into 3 levels: I, II and III. The health posts and primary health care centers offer Level I care with services of newborn care, district hospitals offer special new born care services (SNCU) and zonal hospitals and other tertiary hospitals offer Neonatal Intensive Care Unit (NICU) services.…”
Section: Discussionmentioning
confidence: 99%